Globetrotting : African American Athletes and Cold War Politics - Thomas, Damion L. (Book collections on Project MUSE., 2012)
This probing history examines government attempts to manipulate international perceptions of U.S. race relations during the Cold War by sending African American athletes abroad on goodwill tours and in international competitions as cultural ambassadors and visible symbols of American values.